Nonylphenol affects myocardial contractility and L-type Ca2+ channel currents in a non-monotonic manner via G protein-coupled receptor 30. (6th August 2015) - Gao, Qinghua; Liu, Shuyuan; Guo, Feng; Liu, Shuice; Yu, Xiangchen; Hu, Huiyuan; Sun, Xuefei; Hao, Liying; Zhu, Tong
Highlights: NP affected the cardiac contractility and I Ca-L at a concentration as low as 10 −12  M. NP enhanced the contractility and I Ca-L in the range of 10 −12 –10 −10  M. NP inhibited the contractility and I Ca-L when NP increased to 10 −8 –10 −6  M. GPR30 is only involved in the effects of NP on I Ca-L at lower concentrations. The non-monotonic effects of NP might be due to the different involvement of GPR30. Abstract: Nonylphenol (NP) is one of the widely spread xenoestrogens (XEs) and is used in the production of industrial and consumer surfactants. In the present study, we examined the acute effects of NP on myocardial contractility to determine its rapid-response cardiac effects in the isolated heart. We also investigated the mechanism of action of NP by determining its effects on the L-type Ca 2+ channel (LTCC) currents ( I Ca-L ) in ventricular myocytes. Lower concentrations (10 −12 –10 −10  M) of NP increased cardiac contractility while higher concentrations (10 −8 –10 −6  M) exhibited opposite effects. These apparently opposing effects suggest that NP has biphasic concentration-dependent rapid effects on cardiac contractility. These non-monotonic changes in contractility correlated with the effects of NP on I Ca-L, indicating that ion channels, as rapidly responding membrane proteins, play a very important role in mediating the rapid-response effects of XEs. Further studies revealed that the G protein coupled receptor 30 (GPR30) mediates the effects of NP on LTCC at lower but not higher concentrations, implying that the differential involvement of GPR30 might be responsible for the non-monotonic effects of NP.